The shape of ideas : an illustrated exploration of creativity - Snider, Grant (Abram Comicarts, 2017)
"Whether you are a creative professional, a student, or a front-porch dreamer, this collection of comics will provide insight into the joys and frustrations of creativity, inspiration, and process" -- page 4 of cover.